Current methods to realize the reproductive function in patients with polycystic ovarian syndrome and chronic endometritis - L. Malanchuk; A. Khmil Doswald (Kazimierz Wielki University, 2021)
Literature review indicates that both polycystic ovary syndrome (PCOS) and chronic endometritis (CE) have a significant role in implantation disorders, one of the main causes of infertility and unsuccessful outcomes of assisted reproductive technologies. Study aim was to analyze the literature on current methods to recover reproductive function in patients with polycystic ovary syndrome and chronic endometritis. Materials and methods. The review analyzed scientific literature published in the past decade, as well as relevant research publications available in the online databases, which were searched using the key words "polycystic ovary syndrome", "endometritis", "comorbidity", and "infertility". Results. While the evidence of positive effects of lifestyle changes on fertility is inconclusive, weight loss is a first-line treatment option recommended for women with PCOS. International guidelines for women with anovulatory PCOS consistently recommendas a second-line option  gonadotropin therapy to induce ovulation if oral first-line induction ovulatory therapy, including aromatase inhibitors and selective estrogen receptor modulators, fails. In regards to the treatment of CE, research supports the use of antibiotic therapy which increases the incidence of pregnancy in women with CE and repeated unsuccessful implantation, infertility of unknown ethoilogy or recurrent miscarriage. Conclusions. Current methods of restoring reproductive function in patients with PCOS and chronic endometritis include a wide range of non-pharmacological and pharmacological treatments of PCOS in combination with antibiotic therapy of chronic endometritis, but their effectiveness remains low, which requires the use of assisted reproductive technologies.